Effect of crop establishment methods on seed germination, seedling mortality and growth of Bt cotton (Gossypium hirsutum) -based intercropping systems - Rajpoot, Sudhir K.; Rana, D.S.; Choudhary, Anil K. (Annals of Agricultural Research, 2016)
A field experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhiduring the (Kharif) season of 2012 to evaluate the effect of crop establishment methods on seedgermination, seedling mortality and growth of Bt cotton (Gossypium hirsutum L.)-based intercroppingsystems. The results revealed that percent germination and mortality of germinated seedlings andfinal plant stand/m2 significantly influenced by methods of crop establishment. Germinationpercentage of cotton seeds was 80.2% under direct sowing which was significantly lower than thegermination percentage (97.5 %) recorded under nursery raised for transplanting the cotton crop.Plant height, leaf area index (LAI) and dry matter/plant recorded under direct sowing of cottonwere significantly higher than transplanted cotton. However, seed cotton yield/ha was 5.23% higherunder transplanted cotton, which might be due to 14-15% higher plant stand under transplantingthan direct sown cotton crop.